Scalable decision support for digital preservation. Issue 4 (10th November 2014) - Becker, Christoph; Faria, Luis; Duretec, Kresimir
Abstract : Purpose: – Preservation environments such as repositories need scalable and context-aware preservation planning and monitoring capabilities to ensure continued accessibility of content over time. This article identifies a number of gaps in the systems and mechanisms currently available and presents a new, innovative architecture for scalable decision-making and control in such environments. Design/methodology/approach: – The paper illustrates the state of the art in preservation planning and monitoring, highlights the key challenges faced by repositories to provide scalable decision-making and monitoring facilities, and presents the contributions of the SCAPE Planning and Watch suite to provide such capabilities. Findings: – The presented architecture makes preservation planning and monitoring context-aware through a semantic representation of key organizational factors, and integrates this with a business intelligence system that collects and reasons upon preservation-relevant information. Research limitations/implications: – The architecture has been implemented in the SCAPE Planning and Watch suite. Integration with repositories and external information sources provide powerful preservation capabilities that can be freely integrated with virtually any repository. Practical implications: – The open nature of the software suite enables stewardship organizations to integrate the components with their own preservation environments and to contribute to the ongoing improvement of the systems. Originality/value: – The paper reports on innovative research and development to provide preservation capabilities. The results enable proactive, continuous preservation management through a context-aware planning and monitoring cycle integrated with operational systems.